Presenting the Model of Effective Factors on Smart Governance in the Country - Ghaem Gheiravani; Mohammad Montazeri; Shams Sadat Zahedi (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to provide a model of factors affecting smart governance in the country. The research method is applicable in terms of purpose, and mixed (qualitative-quantitative) in terms of its implementation, and descriptive-survey type in terms of data collection. The statistical population in the qualitative section includes 28 university experts familiar with the subject, who were selected in a non-probability and judgmental manner. The statistical population in the quantitative part includes all the managers and experts working in South Khorasan governorate and Birjand city governorate of planning administration equal to 420 people, and the sample number was selected using Cochran's formula of 200 people. The sampling method in this section was done in a random stratified manner. A semi-structured interview and a researcher-made questionnaire taken from the qualitative section were used to collect information. In the qualitative part, the fuzzy Delphi method was used, and the data from the interviews were coded and analyzed in the three main stages of open coding; axial coding; and selective coding, and SmartPLS 3 software was used in the quantitative part of factor analysis, and SPSS 22 software was used for analysis. The results of the research in the qualitative part showed that three categories of background factors (equipment and infrastructure, required resources, information and communication technology, statistics and intelligent information, and formation platform), content (cyber security, strategy formulation, intelligent management and intelligent planning) and Structural (smart readiness, smart architecture, and smart administration) are effective on the formation of smart governance in the country. The results of the quantitative section showed that the model is of good quality. Extended Abstract Introduction The evolution of human knowledge shows that along with the change in the nature and form of the problems facing mankind, the knowledge packages suitable for the management of such problems have also undergone evolution. One of the important human knowledge that plays an important role in the survival and health of societies is the knowledge of governance and management of public affairs. Therefore, political systems should choose their appropriate style of governance according to the social, political, economic and cultural environment governing the society (Hoseini et al, 2022). One of the most important opportunities that information technology presents to statesmen and managers is increasing accessibility, strengthening efficiency and re-engineering the architecture of the government and the possibility of making it more responsive. The use of information technology in the governance process has led to the emergence of a reality called "smart governance" which is a prerequisite for governing information societies (Mohammadi et al, 2021). Smart governance is about relationships between private, public, economic and social stakeholders and focuses on citizen participation (Lopes & Oliveira, 2017). This style of governance is based on a transparent management system that allows citizens to participate in the planning and decision-making process in terms of the development of their communities, and ensure free access to information (Penaska & Velas, 2019). Smart governance uses information and communication technology to improve democratic processes and public services (e-government), support and facilitate planning and decision-making (Camero & Alba, 2019). Based on this, the researcher of the present study intends to answer the main question: what model of effective factors is suitable for smart governance in the country? Theoretical framework Smart governance Smart governance refers to the intelligent use of information and communication technology to improve decision-making through better collaboration between different stakeholders, including government and citizens. In this case, tools based on information and communication technology, such as social media and the openness of the political space, can be factors that increase citizen interaction and support the development of new governance models for the smart government. Smart governance may also play an important role in smart city initiatives that require complex interactions between governments, citizens, and other stakeholders (Nasri & Tabarzad, 2020). Smart governance is a style of management that is formed based on the intelligent participation of citizens through information and communication technology. This new form of governance transforms citizens from passive consumers of city services to active actors who can comment on the type of services they need (Mohammadi Dehchshme & Moradi, 2021). In other words, this type of governance is based on a transparent management system. This should allow citizens to participate in the planning and decision-making process in terms of city development and ensure free access to information (Penaska & Velas, 2019). Research background Chegni & Koshtar Haranki (2022), examined "smart (knowledge-based) governance relying on the development model (functions of thinker boards)", to explain the concept of thinker board as a strategic and influential institution on the country's decision-making and policy making process and drawing and presenting a local and ecologically compatible model of governance in Iran from this strategic institution. The findings of this research showed that the Islamic Republic's thinker boards at the macro level can help to make the country's governance system smarter and knowledge-based, and in addition to the common functions; it can have functions such as the governing body, guiding and directing the country's macro policies, protection and supervision, explaining the basics, concepts and theoretical frameworks, discourse maker, observation and production of thought, strength of the internal structure of power, socialization and grounding of modern Islamic civilization, use of popular participation and mobilization in the matter of political research and decision making and consultation and problem solving. Hamghadam et al, (2022) investigated "presenting future scenarios of smart urban governance (case study: Rasht city)". The results of the analysis showed that the appropriate foundation scenarios in the field of citizenship education and raising awareness, popular participation and citizenship and private sector participation, making arrangements to increase the budget in the field of smartness, and municipal support of the smart government have the most adaptive value in the future of smart urban governance of the city of Rasht. Research methodology The current research is applicable in terms of purpose, and mixed (qualitative-quantitative) in terms of its implementation, and descriptive-survey type in terms of data collection. The statistical population in the quantitative part includes all the managers and experts working in South Khorasan Governorate and Birjand City Governorate of planning administration, which was identified as 420 people based on internal statistics. Also, the sampling method in this section was done in a random stratified manner. The number of samples was obtained using Cochran's formula considering that the number of people in the studied society was 200. The statistical population in the qualitative section includes 28 university experts familiar with the subject, who were selected in a non-probability and judgmental manner. In this research, the research strategy is of a mixed type (qualitative-quantitative) that after defining the topic and conducting preliminary exploratory and library studies and semi-structured interviews, the relevant factors and components are determined through the Delphi method, which is considered a qualitative research method, by a researcher-made questionnaire (including the answers of the five-choice Likert range and an open question to add possible new components) according to academic and professional experts familiar with the subject, And after receiving their qualitative and quantitative corrective opinions (prioritization of factors) based on the statistical methods of analysis, and finally, through three rounds of going back and forth of the fit of the model, components, and combination of factors reached the consensus of the elites. Research data collection tools are a) library studies (foreign and domestic books and publications, databases, internet sites, etc.); b) semi-structured interviews with academic experts and specialists in the field of governance and information technology; c) a questionnaire. In the qualitative part, the data obtained from the interviews were analyzed in the first stage using three stages of open, central and selective coding; and in the quantitative part, the required data were collected through a questionnaire with closed questions, and in order to analyze them, confirmatory factor analysis test was used in SmartPLS 3 software environment. Also, SPSS 22 software environment was used to analyze the data collected in the descriptive statistics section and determine Cronbach's alpha to check the reliability of the data collection tool.